Correction: Tyrosine bioconjugation with hypervalent iodine. Issue 2 (15th December 2022) - Declas, Nina; Maynard, John R. J.; Menin, Laure; Gasilova, Natalia; Götze, Sebastian; Sprague, Jakob L.; Stallforth, Pierre; Matile, Stefan; Waser, Jerome
Abstract : Correction for 'Tyrosine bioconjugation with hypervalent iodine' by Nina Declas et al., Chem. Sci., 2022, 13, 12808–12817, ; https://doi.org/10.1039/D2SC04558C .